WAYS OF ECONOMIC DEVELOPMENT OF REGIONS: FOREIGN EXPERIENCES AND PRINCIPLES - Toshalieva Saodat Tokhirovna (The Conference Hub, 2025)
In developed countries, modern social reproduction can be described as innovative processing, the basis of which is new innovative knowledge, advanced information technologies, information services and products. Advanced education and information-technological innovations are a decisive factor in economic growth and increasing competitiveness.